The Rising Era of “Immunoporosis”: Role of Immune System in the Pathophysiology of Osteoporosis - Srivastava RK; Sapra L (Dove Medical Press, 2022)
Rupesh K Srivastava, Leena Sapra Immunoporosis Lab, Department of Biotechnology, All India Institute of Medical Sciences (AIIMS), New Delhi, 110029, IndiaCorrespondence: Rupesh K Srivastava, Tel +91 11-26593548, Email rupesh_srivastava13@yahoo.co.in; rupeshk@aiims.eduAbstract: Discoveries in the last few years have emphasized the existence of an enormous breadth of communication between bone and the immune system in maintaining skeletal homeostasis. Originally, the discovery of various factors was assigned to the immune system viz. interleukin (IL)-6, IL-10, IL-17, tumor necrosis factor (TNF)-α, receptor activator of nuclear factor kappa B ligand (RANKL), nuclear factor of activated T cells (NFATc1), etc., but now these factors have also been shown to have a significant impact on osteoblasts (OBs) and osteoclasts (OCs) biology. These discoveries led to an alteration in the approach for the treatment of several bone pathologies including osteoporosis. Osteoporosis is an inflammatory bone anomaly affecting more than 500 million people globally. In 2018, to highlight the importance of the immune system in the pathophysiology of osteoporosis, our group coined the term "immunoporosis". In the present review, we exhaustively revisit the characteristics, mechanism of action, and function of both innate and adaptive immune cells with the goal of understanding the potential of immune cells in osteoporosis. We also highlight the Immunoporotic role of gut microbiota (GM) for the treatment and management of osteoporosis. Importantly, we further discuss whether an immune cell-based strategy to treat and manage osteoporosis is feasible and relevant in clinical settings.Graphical Abstract: Keywords: immunoporosis, innate immune cells, adaptive immune cells, bone cells, gut microbiota, osteoporosis